Assessment of Imbalance among Environmental and Economic Performance within Malaysian Manufacturing Industry: A Sustainable Approach - Khan, Noor Ullah; Rasli, Amran Md.; Hassan, Mohamed Ayyub; Noordin, Nurul Farhana Mohd; Aamir, Muhammad (International Journal of Energy Economics and Policy, 2017)
Sustainability has emerged as a key area of concern especially for manufacturing industry to address major environmental issues. Carbon dioxide (CO2) emission has increased rapidly over the past few decades resulting in harmful outcomes such as global warming, climate change, water and air pollution and degrading environmental performance. The objective of this study is to assess a descriptive study evaluate the imbalance between economic and environmental performance of Malaysian manufacturing industry in general. Secondary data of both economic performance and environmental performance (2011-2016) was descriptively examined. The findings are revealed a significant imbalance between two indicators. In addition, this study also proposed a conceptual model based on previous literature how to reduce this imbalance and create sustainable performance within Malaysian manufacturing firms. Keywords: Environment, CO2 Emission, Environmental Performance, Economic Performance, sustainability JEL Classifications: L6, Q5, Q50, Q51